Pengaruh Pupuk Hidroponik Sebagai Media Alternatif Pengganti Media MS Terhadap Pertumbuhan Anggrek Dendrobium sp. Secara Kultur Jaringan - Tanjung, Ayu Medang; Asnawati, Asnawati; Arifin, Nur (Jurnal Sains Mahasiswa Pertanian, 2019)
Pengaruh Pupuk Hidroponik Sebagai Media Alternatif Pengganti Media MS Terhadap Pertumbuhan Anggrek Dendrobium sp. Secara Kultur Jaringan Ayu Medang Tanjung(1), Asnawati(2), Nur Arifin(3)1Budidaya; UniversitasTanjungpura2Budidaya; UniversitasTanjungpura3Budidaya; UniversitasTanjungpurae-mail:*1ayumdg@gmail.com ABSTRACTThe growth medium in tissue culture has a great influence on growth and development of explants. There are some constrain in obtaining common tissue culture medium, such as hard to make, the chemicals is hard to find and the price is relatively high so it needs an alternative medium that is easily obtained and be able to give the same effect with commonly used tissue culture medium. Hydroponics fertilizer can be used as an alternative medium because it is easy to make and relatively low price compared to MS medium. The research aims to determine wether hydroponic fertilizers can be used as an alternative medium and to find the best type of hydroponic fertilizer to the growth of Dendrobium sp. orchid on tissue culture. The research was conducted from December 20, 2017 to March 20, 2018 at the Laboratory of Biotechnology Faculty of Agriculture, Tanjungpura University. This research used Completely Randomized Design (CRD) with one factor i.e. MS, WB Mix, Nutrisi Hidroponik, Veggie Mix, and Goodplant. The variables observed in this research include the increase number of leaves (piece), the increase number of root (piece), the time to buds appearance (weeks) and number of buds (buds). The results showed that in general the use of hydroponic fertilizer as alternative medium for tissue culture medium provide equal response with MS medium to the growth of Dendrobium sp. orchids, but on MS medium the growth of buds is faster than all types of hydroponic fertilizer as alternative medium. Keyword : Alternative Medium, Dendrobium sp. Orchid, MS Medium, Tissue Culture